Baltic ē‑stems revisited - Kortlandt, Frederik (Baltistica, 2020)
Balto-Slavic ē‑stems represent Proto-Indo-European root nouns, in particular *dheH1‑, and H1‑stems, especially proterodynamic iH1‑stems denoting deverbal abstracts, as well as Proto-Balto-Slavic ē‑extensions of root nouns and hysterodynamic iH2‑stems. In Latin we similarly find PIE root nouns and H1‑stems, especially proterodynamic iH1‑stems denoting deverbal abstracts, and hysterodynamic iH2‑stems denoting denominal abstracts and collectives.